Peran Perempuan Di Dalam Dunia Politik - Ni Luh Ketut Sukarniti (Universitas Mahendradatta Denpasar, 2019)
Politics is an activity in a system or State that involves the process of determining the purposeof the system. Political life in a country especially Indonesia is very complex. The appearanceof women in the political world has been going on from ancient times starting from the days of thekingdoms in the archipelago.The equality of women’s rights in various fields of life is an agenda in this day and age. Theachievements and skills shown by women have led to the notion that there are not many differencesbetween men. His achievements and skills can be seen from the role of women in political life inour country. Strength in the form of toughness, firmness as well as being a condition for becoming aleader.The burden and responsibility of a woman leader is greater than men’s responsibility, wherewomen play a dual role who also has responsibilities both housewives and other female responsibilities.Alignment between women and men is an effort that is not in vain if women try according to theirabilities, to be able to compete with men in accordance with their femininity. From this, many womenhave barriers to entering the political arena. Starting from a lack of awareness to participate in politics.To overcome the obstacles that women have in politics and must make efforts to increase women’sparticipation in the political arena by providing education from an early age, so that women canunderstand. The involvement of women in the political world is still very unbalanced, therefore men’spolicies are lacking in a gender perspective so that decisions often do not favor women, do not payattention to women and do not make women more developed.